AUXILIARY PREMISE THE PEOPLES OF SOUTHERN DAGESTAN IN THE XIX-BEGINNING. XX CENTURY. (ETHNO-ECOLOGICAL ASPECT) - Ramazanova, Zoa Buttaevna; Sulejmanova, Sevda Alievna (History, Archeology and Ethnography of the Caucasus, 2020)
Basing on field ethnographic material, collected in various years in South Dagestan, the article describes economic buildings of the 19th – 20th centuries. Such auxiliary premises and structures, which had additional (utility) functions, affected not only the size of the household, but also determined its appearance, the layout of the housing and utility complex, the composition of building materials, the size and development of the yard, and the sanitary condition. The study points out the attachment to the dwelling of the pantry for groceries and other functional buildings.The authors use general scientific methods (analysis, synthesis), allowing to consider the role and place of utility buildings in the ethnic culture of South Dagestan, as well as to reveal distinctive features related to various ecological conditions. Along with general scientific methods, the study uses private research methods: identification of particular, descriptive method, etc. The article shows that the considered auxiliary (utility, ancillary) buildings performed two main ecological functions: a) storage of food products and household tools (barn, sheds); b) livestock housing.The location of the utility buildings, depending on the geographical features of the area, was of accommodating nature. As we learned, the open type of the yard was the most advantageous one from the ecological point of view: more convenient for drying out after various kinds of precipitation and for airing.
Keywords: outbuildings; products; barn; shed; sheepfold; barn.